p-Bromophenacyl bromide modification of Bothrops asper myotoxin II, a lysine-49 phospholipase A2, affects its pharmacological activities - Díaz Oreiro, Cecilia (1993)
Modification of Bothrops asper myotoxin II, a lysine-49 phospholipase A2 variant, was carried out with p-bromophenacyl bromide. Modified toxin did not show changes in its charge and immunological properties but two of its pharmacological activities were modified. Myotoxic activity, measured by histology and by increment of creatine kinase levels in plasma of mice, was significantly reduced after toxin modification. In addition, liposome disruption activity was also significantly lower with the modified toxin both at 3 and 24 hr of incubation with the alkylating reagent. Some of the implications of these results on the structure-function relationship of myotoxins are discussed.